Variation of Isoprenoid GDGTs in the Stratified Marine Water Column: Implications for GDGT-Based TEX86 Paleothermometry - Guo, Jinqiang; Yuan, Huamao; Song, Jinming; Qu, Baoxiao; Xing, Jianwei; Wang, Qidong; Li, Xuegang; Duan, Liqin; Li, Ning; Wang, Yingxia (Frontiers in Marine Science, 2021)
Isoprenoid glycerol dialkyl glycerol tetraether (isoGDGT) derived from archaea is a lipid biomarker that exhibits high sensitivity to the change in water temperature, leading to the widespread application of the isoGDGT-based TEX86 in surface seawater temperature reconstruction. However, there remain some uncertainties regarding the robustness of TEX86 under changing water conditions (e.g., variations in water depth, oxygen and pH). To better constrain the temperature records of TEX86, we determined isoGDGTs in suspended particles at different depths of the East China Sea during summer 2020. Our data showed that the isoGDGTs were mainly derived from planktonic Thaumarchaeota as revealed by the low ratio of isoGDGT-0/crenarchaeol (< 0.5). The vertical distribution of isoGDGT concentration depicted a downward increase from surface to bottom. This depth trend is likely shaped by the Thaumarchaeota which regulate the extent of ammonia oxidation based on the availability of ammonium. The occurrence of maximal isoGDGT concentrations in bottom layer suggests that the isoGDGTs in sediments are mainly controlled by the bottom archaeal production rather than the surface, and sedimentary TEX86 is more inclined to be a proxy for the bottom water temperature. In addition, the positive bias of TEX86 driven by low dissolved oxygen and low pH was observed under the pycnocline, indicating that the application of TEX86 to reconstruct seawater temperature should be carefully appraised in environments with strong water column stratification.